TEACHING WRITING A HORTATORY EXPOSITION TEXT TO SENIOR HIGH SCHOOL STUDENTS BY USING AN ADVERTISEMENT - Vivi Alfatia; Muhammad Al-Hafizh (Universitas Negeri Padang, 2013)
The use of advertisement can assist students in writing hortatory exposition text. The advertisementis given to students at the pre-writing stage. The type of advertisement that is used is electronic products that show a new product such as mobile phone, television, laptop etc. By looking at the advertisement, the students will be easier to get ideas to write. Then, the teacher makes the hortatory exposition text based on the ideas of the students on the topic in the advertisement. After that, the teacher gives another advertisement with the different topics. Then, the teacher divides the students in a group to write a hortatory exposition text based it provided. After finishing writing, the teacher checked the students' writing with other groups. At the end of the teaching, the teacher concludes material. ABSTRAK Penggunaan iklan untuk membantu siswa dalam menulis teks hortatory exposition. Iklan diberikan kepada siswa pada tahap pra-menulis. Iklan yang digunakan adalah iklan produk electronik yang menunjukkan suatu produk terbaru seperti iklan mobile phone, televisi, laptop, dan lain-lain. Dengan melihat iklan, siswa akan lebih mudah untuk mendapatkan ide-ide untuk menulis. Kemudian guru membuat teks hortatory exposition berdasarkan ide-ide dari siswa tentang topik dalam iklan tersebut. Setelah itu, guru memberikan iklan dengan topik yang berbeda. Kemudian, guru membagi siswa dalam bentuk kelompok untuk menulis teks hortatory exposition berdasarkan iklan yang diberikan. Setelah selesai menulis, guru memeriksa hasil tulisan siswa bersama kelompok lainnya. Di akhir pengajaran, guru menyimpulkan materi. Kata kunci: an Advertisement, produk teknologi, writing at Senior High School